Impact of pretreatment second look 18FDG-PET/CT on stage and treatment changes in head and neck cancer. (November 2021) - Elicin, Olgun; Vollnberg, Bernd; Shelan, Mohamed; Riggenbach, Elena; Bojaxhiu, Beat; Mathier, Etienne; Giger, Roland; Aebersold, Daniel M.; Klaeser, Bernd
Highlights: The potential value of a second look PET/CT prior to radiotherapy was investigated. New lymph node metastases were discovered in half of the patients. Progression of the primary tumor and distant metastases were also observed. This strategy led to changes in treatment planning in more than half of the cases. Abstract: Background: Patients diagnosed with locoregionally advanced head and neck squamous cell carcinoma (LAHNSCC) regularly undergo staging with 18 F-FDG PET/CT in our center. In cases of delays in radiotherapy (RT) planning CT more than 4 weeks after initial PET/CT or clinically suspected progress, PET/CT is repeated for restaging and as an RT planning reference. Our aim was to determine the impact of second-look PET/CT on stage migration, treatment change and RT planning. Methods: Consequent treatment changes were categorized as minor and major. Minor changes were defined as PET/CT-based modifications of RT plans, e.g., the addition of anatomical compartments, changes in high- and low-risk dose levels or both. Major changes included changes from curative to palliative treatment intent and alterations of interdisciplinary treatment plans, such as the addition of induction chemotherapy, switch to primary surgery, no treatment and/or the necessity of additional diagnostic work-up resulting in the postponement or cancellation of treatment. Results: Thirty-two newly diagnosed LAHNSCC patients who were treated between 2014 and 2018 underwent second-look PET/CT (median interval 42.5 days). Second-look PET/CT led to locoregional and distant upstaging in 3/32 and 1/32 patients, respectively. In 1/32 patients (3%), second-look PET/CT led to a palliative approach with systemic treatment. New lymph node metastases were discovered in 16 patients, 6 of whom also showed significant progression of the primary tumor, resulting in minor changes in 16 of the remaining 31 patients (52%) who were treated curatively. Conclusion: If RT treatment planning of LAHNSCC was delayed by more than 4 weeks after initial PET/CT staging or when progression was clinically suspected, a second look at 18 FDG-PET/CT was performed. This led to changes in treatment planning in more than half of the cases, which is expected to directly influence oncologic outcomes.